"EU AGAINST FAKE NEWS – THE NEED FOR POLICY ACTION COUNTERING ONLINE DISINFORMATION" - Runcheva Tasev, Hristina; Apostolovska-Stepanoska Milena (St. Kliment Ohridski University Press Soﬁa • 2019, 2019)
The EU is facing one of the major and evolving challenges of the digital era: the exposure of citizens to large-scale disinformation or fake news. This phenomenon has a bigger impact than ever, as everyone can easily post and share news online and social media contribute towards effortless speeding up the spread of news. This may negatively inﬂuence the democratic processes and societal debates.Comprehensive policy response ahead of European Parliament elections is necessary to avoid the risks of integrity of information and to the integrity of elections. The paper argues that the policy initiatives of the European Commission have a signiﬁcant impact, but a coordinated, joint and sustainable action is needed for a comprehensive response to the evolving online news market.The paper identiﬁes the various actors involved in the dissemination of disinformation and it addresses the possible policy actions at the EU level. It refers to the legal basis for possible policy measures to counter disinformation operations, where the right to freedom of expression must be balanced with the right to be properly informed. The authors recommend actions based on: i) media policy based on media pluralism and diversity of sources; ii) media education and media literacy on citizens’ empowerment; and iii) promotion of responsible informing behavior.
Keywords: disinformation, fake news, media policy, media literacy, freedom of expression.